Assessment of the Demand for Occupational Therapy Upgrade Programs from Diploma to Degree in Kenya (London Journal of Research In Humanities and Social Sciences, 2025)
Occupational therapy (OT) education and training in Kenya has been in existence for over 50 years but stagnated at diploma level qualifications until 2012 when two (2) Kenyan universities established the diploma to degree upgrade programs. This study intended to assess the need, demand, and uptake for OT upgrade programs offered in Kenya. Quantitative exploratory design was utilized. The target population comprised of practicing OTs with diploma qualifications who have not registered for upgrade degree programs (Group 1 – G1); and OTs who have either graduated from or enrolled in an upgrade degree program in Kenyan University (Group 2 – G2). The national research licensing and Institutional Research Boards (IRB) approved the study. Simple random sampling was conducted on a population of 259 members of a Kenya Occupational Therapy Association (KOTA) online forum to select G1. Census sampling was conducted on 108 ongoing and graduated occupational therapists from two universities to select G2. Two separate structured online questionnaires were administered toG1 and G2. Only 108 of approximately 2000 diploma holders trained in Kenya have registered for upgrade degree programs (0.054%). The study findings revealed a significant difference between the G1 and G2 groups t (23) = -2.769, p = .008 at p < .05 in the knowledge and competency levels. The greatest demand for upgrade programs was in the 21 to 30 years’ age group at 52% (G1, n=78). This study provides baseline data to inform further development and strengthening of existing and future OT education curricula in Kenya.
Keywords: brazil; multimorbidity; multiple long-term chronic conditions; socioeconomic positions; inequality measures; health inequalities; literature; image; Perrault; Dor; Ibarbourou; Higher education; developing countries; Educational technology; Generative AIs; curriculum; Occupational therapy; upgrade programs; competencies; diploma